Implementasi Kebijakan Penggunaan Sistem Keuangan Desa Di Kabupaten Sukabumi - Umam, Khaerul; Maolani, Dedeng; Rahman, Widi Maulana (Publica: Jurnal Pemikiran Administrasi Negara, 2018)
The Cipeundeuy Village Government runs the Village Financial System, but the implementation still has several problems, including lack of facilities and infrastructure, lack of human resources and communication capabilities that are not going well. The purpose of this research is to find out how to implement the Village Financial System (SISKEUDES) Policy in Cipeundeuy Village. This study uses the theory of the implementation of Van Horn and Van Metter in Agustino (2014). The method used is descriptive qualitative. Data collection techniques used were interviews, observation, and documentation. Analysis of the data used is the Hubberman model in Mukhtar (2017). The results showed that the implementation of the use of siskeudes has not gone well. This can be seen from the lack of infrastructure, lack of human resources and communication capabilities that are not going well. Suggestions that can be given are the fulfillment of supporting facilities, there must be a shared desire to run the siskeudes and improve and strengthen communication patterns.